A Fuzzy-Logic based Resource Levelling Optimisation Tool. Issue 3 (2015) - Iyer, Parth; Liu, Yuxin; Sadeghpour, Farnaz; Brennan, Robert W.
Abstract: This paper focuses on the development of a Resource Levelling tool that uses Fuzzy Logic to optimise the standard or "Exact" method for resource levelling on a project. Unlike extant resource levelling tools that use fuzzy logic in conjunction with other artificial intelligence techniques such as genetic algorithms, our proposed approach is an independent resource levelling algorithm that is based on fuzzy logic. The paper describes a MATLAB implementation of the algorithm along with results from an example project. Based on these results, the proposed algorithm appears to provide superior resource levelling performance when compared to traditional resource levelling approaches.